Solah Bawa Free Movement as a Whole Person Art Practice - Purwanti Kusumaningtyas (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
Solah bawa, a meditative free movement dance, was developed by Sitras Anjilin (the head of Padhepokan Seni (art center and workshop) Tjipta Boedaja, Tutup Ngisor, Kabupaten Magelang, Central Java). A participatory observation towards a group named Komunitas Sabtuan, guided by Sitras Anjilin, and an etic interpretive analysis of the activity’s details found that solah bawa free movement reflects whole person aspects of human quality development. This article explicates how such art activity as free movement dance can be done by individuals to enhance whole person development. It argues that regular art practice can help individuals develop themselves holistically, and thus, it can promote balanced life.